Detection of hepatitis E virus RNA in saliva for diagnosis of acute infection. (16th April 2018) - Rivero‐Juarez, A.; Frias, M.; Lopez‐Lopez, P.; Martinez‐Peinado, A.; Risalde, M. Á.; Brieva, T.; Machuca, I.; Camacho, Á.; García‐Bocanegra, I.; Gomez‐Villamandos, J. C.; Rivero, A.
Summary: Diagnosis of acute hepatitis E virus (HEV) infection is established by detection of anti‐HEV IgM antibodies by ELISA or by amplification of serum viral RNA. Here, we evaluate the diagnostic value of testing HEV RNA in saliva to identify patients with acute HEV infection. Prospective proof‐of‐concept study including patients with acute hepatitis. Whole blood and neat saliva samples were obtained from all patients. Saliva samples were processed and analysed for HEV RNA by RT‐PCR within 2 hr after collection. A total of 34 patients with acute hepatitis and 12 healthy donors were included in the study. HEV RNA in serum was confirmed by RT‐PCR in eight of these patients (23.5%; 95% CI: 12.2%–40.2%). HEV was isolated in the saliva of eight of 34 patients (23.5%; 95% CI: 12.2%–40.2%). All patients with HEV RNA amplified in saliva had detectable HEV RNA in serum. HEV was isolated neither in the saliva of any of the 26 patients without detectable HEV RNA in serum nor in healthy donors. Our study suggests that acute HEV infection could be diagnosed by assessing viral load in saliva.